Algebra Question !

allyonline

New member
Joined
Aug 26, 2010
Messages
19
My problem is (-2p^2)(-p^9). I looked in the back of the book, and the answer says : 2p^11. I Just want to know why, and why is nothing negative. If someone could walk me through the steps, that would be wonderful!
 
allyonline said:
My problem is (-2p^2)(-p^9).
RULE: (a^x)(a^y) = a^(x+y)

(-2p^2)(-p^9)
= -2(p^2)-1(p^9)
= -2(-1) (p^2)(p^9)
= 2p^(2+9)
=2p^11

didya follow all that?
 
Yeah ! Thanks I followed that, but I'm confused some on your second step, why did you take those two numbers out of the parenthesis ?
 
Simply to show (clarify) that this can be done!
Like, -1 = 1 times -1 or 1(-1) : a bit ridiculous, yes, but still a fact
 
Denis said:
allyonline said:
My problem is (-2p^2)(-p^9).
RULE: (a^x)(a^y) = a^(x+y)

(-2p^2)(-p^9)
= -2(p^2)(-1)(p^9)
= -2(-1) (p^2)(p^9)
= 2p^(2+9)
=2p^11

didya follow all that?

You're gonna have to group that (-1) there, Denis. Otherwise, it's not a factor. Picky, I know, but I haven't posted anything today. So you get picked on.
 
Top